Implementation of Artificial Neural Network for Predicting Oil Palm Production Results Using Backpropagation - Eki Komariah; Barry Ceasar Octariadi; Alda Cendekia Siregar (STMIK Banjarbaru, 2023)
The largest plantation in Indonesia is the palm oil plantation. One of the private palm oil plantations is PT. Kebun Ganda Prima, Kembayan Estate. This company has uncertain production yields, making it unable to determine future production results. Therefore, a prediction of palm oil fruit production is needed as a reference to understand future production yields. The prediction results can be used by the company to improve production outcomes and prevent losses from falling short of targets. This research utilizes the JST-backpropagation, which has the advantage of repeated learning, resulting in a robust and consistent system. The testing was conducted with several parameters, including 3 hidden layers, 2,000 epochs, a learning rate of 0.3, and an error goal of 0.001. The obtained prediction results indicate a Mean Squared Error (MSE) of 0.11249 with an accuracy of 88%.Keywords: Artificial Neural Network; Backpropagation; Prediction; Palm Oil.AbstrakPerkebunan terbesar di Indonesia adalah perkebunan kelapa sawit. Salah satu perkebunan kelapa sawit Swasta ialah PT. Kebun Ganda Prima, Kembayan Estate. Perusahaan ini memiliki hasil produksi yang tak menentu sehingga tidak dapat menentukan hasil produksi dimasa mendatang. Oleh karena itu, diperlukan prediksi hasil produksi buah kelapa sawit untuk dijadikan acuan agar mengetahui hasil produksi di masa mendatang. Hasil prediksi nantinya dapat digunakan oleh pihak perusahaan untuk meningkatkan hasil produksi agar tidak mengalami kerugian dari target dan hasil yang telah dibuat. Penelitian ini menggunakan JST-backpropagation yang memiliki kelebihan karena pembelajarannya dilakukan berulang sehingga dapat mewujudkan sistem yang tahan akan kerusakan dan konsisten bekerja dengan baik. Pengujian ini dilakukan dengan beberapa parameter yaitu hidden layer 3, epoch 2.000, learning rate 0,3 dan untuk error goal 0.001. dari hasil prediksi yang di dapat yaitu hasil tingkat Error Mean Squared Error (MSE) yang didapatkan adalah 0,11249 dengan akurasi 88.%.